2022
DOI: 10.1002/jgh3.12780
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of oral semaglutide in patients with non‐alcoholic fatty liver disease complicated by type 2 diabetes mellitus: A pilot study

Abstract: Background and Aim: This study aimed to clarify the efficacy and safety of oral semaglutide treatment in patients with non-alcoholic fatty liver disease (NAFLD) complicated by type 2 diabetes mellitus (T2DM). Methods: This was a single-arm, open-label pilot study. Sixteen patients with NAFLD who received oral semaglutide for T2DM were included in the analysis. Oral semaglutide was initiated at a dose of 3 mg once daily, and the dose was sequentially increased to 7 mg at 4 weeks and 14 mg at 8 weeks (maintenanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 45 publications
4
9
0
Order By: Relevance
“…Similarly, satisfactory effects on liver steatosis but not liver stiffness were confirmed in a study using magnetic resonance imaging to assess changes in liver parenchyma [ 44 ]. Finally, a very recent pilot study tested the oral formulation of Semaglutide for 24 weeks in 16 TD2 patients with NAFLD, showing results consistent with our findings [ 45 ].…”
Section: Discussionsupporting
confidence: 89%
“…Similarly, satisfactory effects on liver steatosis but not liver stiffness were confirmed in a study using magnetic resonance imaging to assess changes in liver parenchyma [ 44 ]. Finally, a very recent pilot study tested the oral formulation of Semaglutide for 24 weeks in 16 TD2 patients with NAFLD, showing results consistent with our findings [ 45 ].…”
Section: Discussionsupporting
confidence: 89%
“…Furthermore, since an elevation of VLDL is commonly observed in an insulin resistant-state [ 9 , 10 ], a decrease of VLDL suggests an improvement of diabetic dyslipidemia due to insulin resistance. Arai et al studied the efficacy and safety of oral semaglutide in 16 type 2 diabetic patients with non-alcoholic fatty liver disease [ 11 ]. In their study, body weight, liver function and HbA1c were significantly improved after 12 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…58,[61][62][63][64][65] A trial has been designed to evaluate oral semaglutide in hepatic steatosis (NCT03884075) and a pilot study has shown that this new drug formulation improves indexes of hepatic steatosis and fibrosis in T2D subjects. 66 It has been shown that GLP-1 RA enhances insulin sensitivity in the liver and WAT and reduces DNL and WAT lipolysis, possibly with a direct effect on the lipolysis pathway, consequently reducing FFA flux to other tissues, [67][68][69] as shown in Table 1. These drugs improve IR in WAT and increase adiponectin levels, improving adipose tissue function and redistributing lipids.…”
Section: Glucagon-like Peptide-1 Receptor Agonistsmentioning
confidence: 99%
“…Exenatide, liraglutide and dulaglutide reduce hepatic fat content assessed by magnetic resonance; liraglutide and semaglutide reduce the histological features of NASH, thus preventing the worsening of inflammation but have no effect on liver fibrosis stages or in NASH‐related cirrhosis 58,61–65 . A trial has been designed to evaluate oral semaglutide in hepatic steatosis (NCT03884075) and a pilot study has shown that this new drug formulation improves indexes of hepatic steatosis and fibrosis in T2D subjects 66 …”
Section: Glucagon‐like Peptide‐1 Receptor Agonistsmentioning
confidence: 99%